PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PRODUK OBRAL DENGAN IKLAN TANPA INFORMASI YANG JELAS - Muhammad Yasid; Nanci Yosepin Simbolon; Boy Chasea Pasi; Ricky Pratama Siregar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
The existence of a product that is sold on sale can benefit parties, (the businessperson and the consumer). However, the existence of hidden conditions in the sale of products sold on these sales, is clearly very detrimental to consumers. In order to be more attractive to consumers in buying sale products, businesses use advertising facilities but unfortunately, most of these advertisements contain information that is not clear, thus violating the rights of consumers, which in the end, consumers also suffer losses. The results of this study indicate that advertisements without clear information on sale products violate the provisions in Law Number 8 of 1999 concerning Consumer Protection, regulated in Article 11 where business actors in the case of sales made through sale or auction are prohibited from deceiving / misleading consumers by: stating goods as if they meet certain quality standards; does not contain hidden defects; not intending to sell the goods offered but with the intention to sell other goods; does not provide goods in certain quantities and / or sufficient quantities with the intention of selling other goods; and raise prices or tariffs of goods before making a sale. The responsibility of business actors in advertising product sales without clear information is to provide compensation to consumers in the form of refunds or replacement of goods (products) of the same type or equivalent in value to losses suffered by consumers.